2021
DOI: 10.1126/sciadv.abc0467
|View full text |Cite
|
Sign up to set email alerts
|

Acoustofluidic centrifuge for nanoparticle enrichment and separation

Abstract: Liquid droplets have been studied for decades and have recently experienced renewed attention as a simplified model for numerous fascinating physical phenomena occurring on size scales from the cell nucleus to stellar black holes. Here, we present an acoustofluidic centrifugation technique that leverages an entanglement of acoustic wave actuation and the spin of a fluidic droplet to enable nanoparticle enrichment and separation. By combining acoustic streaming and droplet spinning, rapid (<1 min) nanopartic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
96
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 148 publications
(109 citation statements)
references
References 64 publications
0
96
0
Order By: Relevance
“…Microfluidic platforms combined with supersonic fields (acoustofluidics) have been extensively used for manipulation and separation of particles in a label-free manner. 100,101 Recent studies from our and other groups have shown that externally applied supersonic waves (either This journal is © The Royal Society of Chemistry 2022 by PZT embedded on the substrate or bulk acoustic resonator) can induce intensive acoustic pressures in the order of hundreds of KPa within the confined microchannel to reform NPs (Fig. 4a).…”
Section: Multiple Field-based Microfluidic Reactorsmentioning
confidence: 99%
“…Microfluidic platforms combined with supersonic fields (acoustofluidics) have been extensively used for manipulation and separation of particles in a label-free manner. 100,101 Recent studies from our and other groups have shown that externally applied supersonic waves (either This journal is © The Royal Society of Chemistry 2022 by PZT embedded on the substrate or bulk acoustic resonator) can induce intensive acoustic pressures in the order of hundreds of KPa within the confined microchannel to reform NPs (Fig. 4a).…”
Section: Multiple Field-based Microfluidic Reactorsmentioning
confidence: 99%
“…[ 71 ] Huang's team developed an acoustofluidic centrifuge for nanoparticle enrichment and separation by entanglement of SAW actuation and the spin of a fluidic droplet (Figure 2g ). [ 72 ] Generally, SAW‐based acoustic nanofilters enable a simple contact­free method for EV isolation in a size‐tunable manner, but the farraginous cell debris and protein aggregates cannot be separated clearly.…”
Section: Advanced Nanotechnologies For Ev Isolationmentioning
confidence: 99%
“…g) Acoustofluidic centrifugation. Reproduced with permission [72]. Copyright 2021, American Association for the Advancement of Science.…”
mentioning
confidence: 99%
“…Acoustofluidics, the fusion of acoustics and microfluidics, can effectively manipulate and sort picolitre droplets via noninvasive, mild, and highly biocompatible acoustic forces. [ 35–53 ] Therefore, acoustofluidic sorters often have advantages in biocompatibility. [ 54–56 ] However, current acoustofluidic droplet sorters have deficiencies in their energy conversion rate, which hinders their further development.…”
Section: Introductionmentioning
confidence: 99%